1992
DOI: 10.1002/1097-0142(19920415)69:8<2036::aid-cncr2820690805>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seven tumor markers (CA 50, CA 19-9, CA 19-9 TruQuant, CA 72-4, CA 195, carcinoembryonic antigen, and tissue polypeptide antigen) in the pretreatment sera of patients with gastric carcinoma

Abstract: Preoperative serum levels of the tumor markers CA 50, CA 19‐9, CA 19‐9 TruQuant, CA 72‐4, CA 195, carcinoembryonic antigen (CEA), and tissue polypeptide antigen (TPA) were measured in 94 patients with well‐staged adenocarcinoma of the stomach and in 15 patients with benign gastric diseases. In all patients with carcinoma, a laparotomy was done. The serum levels were correlated with the stage of disease, the location of the primary tumor, and the resectability and grade of differentiation. The marker CA 50 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 7 publications
3
23
2
Order By: Relevance
“…According to these investigators a weak correlation was found with CA19.9 positivity and tumor location .No correlation existed between CA19.9 positivity, age, tumor size, histological type, lymph node, hepatic and peritoneal metastasis (2). Wobbs et al (3) have compared the levels of CA19.9 with stages of the gastric cancer. In patients of stage IV gastric carcinoma CA19.9 levels as high as 2300 U/ml have been reported.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…According to these investigators a weak correlation was found with CA19.9 positivity and tumor location .No correlation existed between CA19.9 positivity, age, tumor size, histological type, lymph node, hepatic and peritoneal metastasis (2). Wobbs et al (3) have compared the levels of CA19.9 with stages of the gastric cancer. In patients of stage IV gastric carcinoma CA19.9 levels as high as 2300 U/ml have been reported.…”
supporting
confidence: 87%
“…Its levels correlate well with pancreatic cancer staging.80% of patients with pancreatic carcinoma, 67% of hepatobiliary, 40-50% of gastric carcinoma patients show high CA 19.9 (>37U/L). Raised levels of this marker in gastric carcinoma has also been reported by various investigators (3,5,6). Yamao et al (7) have shown elevation of CA 19.9 levels in 26 patients of gastric carcinoma with mean value of 163 U/ mL range being (53.8-873.5).…”
mentioning
confidence: 53%
“…Particularly in patients with stage II or stage III gastric cancer, there was a significant difference between HGF CAl9-9 and CA125. Recently, various tumour markers for gastric cancer were reported from many clinical institutes, including CA72-4, TPA and CA50 (Guadagni et al, 1992;Wobbes et al, 1992). However, after a review of the literature, the measurement of serum HGF levels seems to be the most sensitive method for monitoring tumour progression in gastric cancer.…”
Section: Discussionmentioning
confidence: 54%
“…A large number of studies on the potential diagnostic value of pleural tumor markers have been published, which report either encouraging or disappointing results (Wobbes et al, 1992;Garcia-Pachon et al, 1997;Riantawan et al, 2000;Paganuzzi et al, 2001). The disagreement in results can be attributed to different factors, including the heterogeneity of tumor types, the appropriate inclusion of paramalignant PE to calculate test performances, the sometimes underpowered series, and the use of different methodologies and cut-off values in tumor marker assays (Porcel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%